The Evolution of Appendicular Muscles During the Fin-to-Limb Transition: Possible Insights Through Studies of Soft Tissues, a Perspective - Mansuit, Rohan; Herrel, Anthony (Frontiers in Ecology and Evolution, 2021)
The evolution of the appendages during the fin-to-limb transition has been extensively studied, yet the majority of studies focused on the skeleton and the fossil record. Whereas the evolution of the anatomy of the appendicular musculature has been studied, the changes in the muscular architecture during the fin-to-limb transition remain largely unstudied, yet may provide important new insights. The fin-to-limb transition is associated with the appearance of a new mode of locomotion and the associated shift from pectoral to pelvic dominance. Here, we propose ways to investigate this question and review data on muscle mass and muscle architecture of the pectoral and pelvic muscles in extant vertebrates. We explore whether changes in appendage type are associated with changes in the muscular architecture and the relative investment in different muscle groups. These preliminary data show a general increase in the muscle mass of the appendages relative to the body mass during the fin-to-limb transition. The locomotor shift suggested to occur during the fin-to-limb transition appears supported by our preliminary data since in ‘fish’ the pectoral fins are heavier than the pelvic fins, whereas in tetrapods, the forelimb muscles are less developed than the hind limb muscles. Finally, a shift in the investment in different muscle groups with an increase of the contribution of the superficial groups in tetrapods compared to ‘fish’ appears to take place. Our study highlights the potential of investigating quantitative features of the locomotor muscles, yet also demonstrates the lack of quantitative data allowing to test these ideas.